Relationship between the foreign language classroom anxiety and Chinese character achievement among Laos Mandarin students - Chew, Fong Peng; Guo, Qing Li; Yeoh, Yin Yin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The main aim of this study was to investigate the relationship between Foreign Language Classroom Anxiety (FLCA) and Chinese character achievement of Mandarin learners in Laos. The sample of the research consisted of 133 (54 females, 79 males) attending a three-year Mandarin course at Hua Qiao Champasak Technology College. The results of Pearson correlation revealed foreign language classroom anxiety was found to be significantly and positively correlated with English achievement (r=0.178, p<0.05). In addition, although independent sample t-test showed there was no significant difference in Chinese character achievement and foreign language classroom anxiety between male students and female students, the mean (M=104.48) demonstrated that females exhibited higher levels of anxiety than males (M=103.47), and females’ achievement (M=23.24) are lower than males (M=24.94). Following these results, certain suggestions were set for foreign language teachers to be aware of foreign language classroom anxiety level, its causes, and results in Mandarin language classroom settings.